Smārikā : ashṭama Bhāratīya Ādivāsī Kalyāṇa Sammelana, Rshabhadeva, Udayapura, 16-17 Aprela 1966 - Śarmā, Kanhaiyālāla (Rājasthāna Ādima Jāti Sevaka Saṅgha], 1970)
Report of the 8th All India Tribal Welfare Conference.